2023
DOI: 10.1186/s12906-023-04067-9
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid and metformin co-administration reduce oxidative stress, apoptosis and inflammation via Fas/caspase-3 and NF-κB signaling pathways in thioacetamide-induced acute hepatic encephalopathy in rats

Abstract: Background Hepatic encephalopathy (HE) is a consequence of chronic or acute liver diseases. This study evaluates the combined effect of gallic acid (GA), and metformin (Met) on the liver and brain damage associated with HE. Methods Acute HE was induced by a single dose of thioacetamide (TAA) (300 mg/kg) as an I.P. injection. Treated groups received GA group (100 mg/kg/day, p.o), Met (200 mg/kg/day, p.o), or their combination for 25 consecutive days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…A study has shown that portulaca oleracea L. enhanced the anti-inflammatory, antioxidant, and autophagic effects of metformin in diabetic rats [21]. It also found that gallic acid enhanced the antioxidant, anti-apoptosis, and anti-inflammatory effects in rats with acute hepatic encephalopathy [22]. Hence, a combination of metformin with natural products might be an effective means of enhancing the efficacy and reducing the toxicity for improving the cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…A study has shown that portulaca oleracea L. enhanced the anti-inflammatory, antioxidant, and autophagic effects of metformin in diabetic rats [21]. It also found that gallic acid enhanced the antioxidant, anti-apoptosis, and anti-inflammatory effects in rats with acute hepatic encephalopathy [22]. Hence, a combination of metformin with natural products might be an effective means of enhancing the efficacy and reducing the toxicity for improving the cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%